Computed tomography scan in supine and prone positions: An alternative method to detect intramural gas in emphysematous cystitis and to evaluate efficacy after adjuvant continuous intravesical irrigation treatment. (April 2013) - Cortés-González, Jeff R.; Ortiz-Lara, Gerardo E.; Salinas, Matías; Hernández-Galván, Fernando; Gómez-Guerra, Lauro S.
Abstract Objective: To evaluate the efficacy of continuous intravesical irrigation with saline plus amikacin as adjuvant therapy and to evaluate the computed tomography (CT) scan in supine and prone positions (CystoCT scan) as an alternative diagnostic and evaluation method of intramural gas in emphysematous cystitis (EC) before and after treatment. Methods: Consecutive patients with a diagnosis of EC who were hospitalized between March 2006 and January 2011 were investigated. The diagnosis was made by CystoCT scan. Treatment consisted of intravenous antibiotics, control of concomitant diseases, and placement of a 3-way urinary catheter for continuous irrigation of 500 mg of amikacin diluted in 1 l of saline given on days 0, 3, and 7. Treatment was considered successful when there was an absence of gas in the bladder wall, the urine culture was negative, there was clinical improvement, and there was an absence of toxicity. Results: Eleven patients were hospitalized with a diagnosis of EC during the study period. Four were excluded from the study, 2 due to the lack of confirmation of the diagnosis with the CystoCT scan. Treatment was successful in all patients; for 6 (86%) this was achieved in 3 days and for 1 (14%) in 7 days. No toxicity was reported. Conclusions: Continuous intravesical irrigation with saline plus amikacin as adjuvant treatment of EC is an inexpensive, effective, and safe tool that might help conventional treatment and provide a rapid recovery. The CystoCT scan is an alternative method to diagnose and evaluate intramural gas in EC patients. These findings should be challenged in a randomized, multi-centre, placebo-controlled clinical trial.